The Role of Technology in the Development of Judicial Work A Study in Iraqi Legislation - Abdul-Ilah Al-Shaya, Fahim (Journal of Legal Studies and Researches, 2023)
This study focuses on the possibility of mixing the precision that characterizes judicial actions. With the means of technology, and the relative character of the latter. This study has reached many conclusions and recommendations, perhaps the most important of which are: the need to legislate a special law that regulates judicial procedures according to the means of technology.